Triheterometallic Lanthanide Complexes Prepared from Kinetically Inert Lanthanide Building Blocks. Issue 15 (20th February 2017) - Sørensen, Thomas Just; Tropiano, Manuel; Kenwright, Alan M.; Faulkner, Stephen
Abstract : Three molecular structures, each containing three different lanthanide(III) centres, have been prepared by coupling three kinetically inert lanthanide(III) complexes in an Ugi reaction. These 2 kDa molecules were purified by dialysis and characterised by NMR and luminescence techniques. The photophysical properties of these heterotrimetallic complexes were investigated and are discussed by comparison with simpler, but related, heterodimetallic compounds. It was found that an aminonaphthalene unit inhibits the sensitisation of terbium, and that the spatial arrangement of the chromophores and lanthanide(III) centres in these molecules inhibits the efficient sensitisation of europium. We conclude that the intramolecular collisions required for efficient Dexter energy transfer from the sensitiser to the lanthanide(III) centre can be prevented by steric congestion. Abstract : We have prepared large distinct heteronuclear lanthanide architectures from kinetically inert building blocks. By combining optical and magnetic resonance spectroscopy, we are able to conclude that conformational freedom allowing for intramolecular collision is more important than apparent proximity for efficient energy transfer.